2004
DOI: 10.1097/00041433-200410000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Control of smooth muscle cell proliferation in vascular disease

Abstract: New insights into mechanisms whereby the extracellular matrix takes part in the control of smooth muscle cell proliferation suggest a number of putative targets for future therapies that can be applied to increase plaque stability, prevent the clinical consequences of atherosclerosis and improve outcomes after interventional procedures and organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 61 publications
0
64
1
Order By: Relevance
“…This study demonstrates that platonin, a trithiazole pentamethine cyanine, inhibits PDGF-BB-stimulated VSMC prolifera- Therefore, the modulation of VSMC proliferation has important therapeutic implications [1] . In the present study, we found that platonin inhibited cell proliferation in PDGF-BBstimulated VSMCs at 1-5 µmol/L.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This study demonstrates that platonin, a trithiazole pentamethine cyanine, inhibits PDGF-BB-stimulated VSMC prolifera- Therefore, the modulation of VSMC proliferation has important therapeutic implications [1] . In the present study, we found that platonin inhibited cell proliferation in PDGF-BBstimulated VSMCs at 1-5 µmol/L.…”
Section: Discussionmentioning
confidence: 83%
“…Abnormal proliferation of vascular smooth muscle cells (VSMCs) is implicated in the pathogenesis of several diseases, including atherosclerosis, restenosis after angioplasty, transplant vasculopathy, and failure of vein graft bypasses [1] . Numerous growth factors and cytokines are reported to be released in human vascular lesions by dysfunctional endothelial cells, inflammatory cells, platelets, and VSMCs, and these mediate chemoattraction, cell migration, proliferation, apoptosis, and matrix modulation [2] .…”
Section: Introductionmentioning
confidence: 99%
“…induces expression of chemokines and recruitment of immune cells [9][10][11], increases expression of adhesion molecules such as vascular cell adhesion molecule 1(VCAM-1) [12]. and stimulates VSMC migration or proliferation [13]. Of these processes, there is increasing evidence that activation of inflammatory responses as a result of leukocytic infiltration and stimulation of macrophage function are necessary for lesion development and tissue remodeling [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Vascular remodeling during disease or injury involves altered expression of extracellular matrix proteins and cell surface integrins. [2][3][4] After arterial injury, laminin expression is reduced and fibronectin accumulates around VSMCs.…”
mentioning
confidence: 99%